Effect of leptin on the gluconeogenesis in calf hepatocytes cultured in vitro. (12th September 2013) - Li, Yu; Li, Xiaobing; Song, Yuxiang; Shi, Xiaoxia; Ding, Hongyan; Yang, Wentao; Liu, Zhaoxi; Chen, Hui; Li, Xinwei; Wang, Jianguo; Liu, Guowen; Wang, Zhe
Abstract: We have investigated the effect of leptin on gluconeogenesis in the liver. Hepatocytes were cultured and treated with 0, 2.5, 5, 10, 50, 100 ng/mL of leptin in groups I, II, III, IV, V, and VI, respectively. mRNA expression and enzyme activity of pyruvate carboxylase and phosphoenolpyruvate carboxykinase were determined by real‐time fluorescence quantitative RT‐PCR and biochemical kits, respectively. Compared with group I, mRNA expression of pyruvate carboxylase and phosphoenolpyruvate carboxykinase in groups III, IV, V, and VI were significantly lower ( P  < 0.01). Pyruvate carboxylase and phosphoenolpyruvate carboxykinase enzyme activity decreased significantly ( P  < 0.05) when leptin concentration exceeded 5 and 10 ng/mL, respectively. These results indicate that leptin markedly downregulated mRNA expression and enzyme activity of pyruvate carboxylase and phosphoenolpyruvate carboxykinase in hepatocytes, which suggests that high concentrations of LP inhibit hepatocyte gluconeogenesis, thus making negative energy balance more serious.